bahasa Inggris - Dewi, Winda Sari; Sahib, Abdul (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
This article discusses the concept of Islamic education service marketing and its implementation in Rejang Lebong Regency, which faces challenges in managing and marketing education. By integrating Sharia values such as honesty, benefit, and sustainability, modern marketing strategies are applied to enhance the competitiveness of Islamic educational institutions. This study employs a qualitative approach through literature review and field observation. The findings reveal that utilizing social media as a promotional tool increases outreach by 30%, while flagship services such as Quran memorization programs and curricula integrating modern Islamic values have boosted student enrollment by 40% over the past two years. Major challenges include limited funding and human resources proficient in Sharia-based and digital marketing. Identified solutions include staff training and optimizing local resources, such as alumni networks. The article concludes that combining Sharia principles, modern marketing strategies, and innovative educational programs is crucial for the sustainability and competitiveness of Islamic educational institutions in the era of globalization. These findings contribute both practical and theoretical insights to the development of Islamic education management.